Effects of Tax Socialization and Tax System Digitalization on Taxpayer Compliance with Tax Knowledge as an Intervening Variable - Devi Saputri; Fitra Dharma; Liza Alvia (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This research aims to analyze the effect of tax socialization and tax system digitalization on taxpayer compliance with tax knowledge as an intervening variable among individual taxpayers in Lampung Province. The research employs a quantitative approach with data collection through questionnaires distributed to 147 individual taxpayer respondents residing in Lampung Province who are over 25 years of age and work as individual entrepreneurs, private employees, or civil servants. Data analysis uses path analysis techniques to examine the direct and indirect effects between variables. The results show that tax system digitalization has a positive and significant effect on taxpayer compliance, both directly and through tax knowledge as an intervening variable. However, the hypothesis stating that tax socialization affects taxpayer compliance is not supported by the research findings. This research model has an R Square value of 0.87, indicating a very strong relationship between tax system digitalization and taxpayer compliance. This research provides important contributions for tax authorities in formulating strategies to improve taxpayer compliance through strengthening tax system digitalization and enhancing tax knowledge.